PERCEPTION OF UNDERGRADUATE STUDENTS OF S.V. AGRICULTURAL COLLEGE REGARDING ONLINE CLASSES DURING THE COVID-19 PANDEMIC - P. BALA HUSSAIN REDDY*, V. SAILAJA and S.V.PRASAD (The Journal of Research ANGRAU, 2020)
The online survey was conducted between June, 2020 and August, 2020 to understand theperception of the undergraduate students of the S.V. Agricultural College, Tirupati regarding onlineclasses. Out of 300 undergraduate students pursuing 1st, 2nd, and 3rd year of B.Sc (Hons.), 72 studentsbelonging to all three years responded. The perception of the students was categorised under fouraspects viz., perception of learning environment, social perception, academic self-perception andperception of students on faculty members.The majority of the students (97.1%) were using smartphonefor attending virtual classes, ranked online lecture supported by a screen shared PowerPoint as thebest virtual teaching method with a weightage of 278 and 3 hrs/day was the comfortable screen timementioned by 50 percent of the students. About 95.7 percent of the students perceived that a realclass environment helps in good understanding than an online learning environment. The majority(87.2%) stated that learning in isolation is not exciting.Less than half (44.10 %) of respondentsexpressed satisfaction, while 55.90% of the respondents expressed dissatisfaction towards virtualclasses.